Effects of glyphosate on egg incubation, larvae hatching, and ovarian rematuration in the estuarine crab Neohelice Granulata - Avigliano, Luciana (2014)
Ovigerous females of the estuarine crab (Neohelice granulate) were exposed to both pure glyphosate (2.5 mg/L and 5 mg/L) and a glyphosate formulation (Roundup Ultramax, containing glyphosate at 2.5 mg/L acid equivalent). At the end of the egg incubation period, a significant reduction in the number of hatched larvae was seen as a result of Roundup exposure. Additionally, several larvae abnormalities were seen in both pure glyphosate (2.5 mg/L) and Roundup treatments, such as hydropsy and hypopigmented eyes, and atrophied eyes were observed in the Roundup treatment. To evaluate the effect of the herbicide on ovarian rematuration, females remained exposed for 32 d. Pure glyphosate at 2.5 mg/L stimulated ovarian maturation over control levels, mainly in terms of a higher gonadosomatic index and a higher percentage of vitellogenic oocytes. A plausible hypothesis to be tested in further experiments is that exposure to glyphosate disrupts the hormonal system controlling reproduction.